Learning Engagement of Children during the Covid-19 Period in Lalbandi Municipality: A Mixed Method - Koirala, Matrika Parsad (Tribhuvan University Journal, 2023)
This paper analyzes the learning status of children and their access to information and communication technology (ICT) during the pandemic period. This study employs a mixed-methods design; selecting two secondary schools were purposively to cover both urban and rural areas in the Lalbandi Municipality of Madhesh Pardesh. Primary data were collected through interview guidelines with the respondents, surveys, focus group discussions, and field notes, while secondary data were collected using various sources, such as policy documents, empirical reports, theoretical literature, and internet sources. Both descriptive and analytical methods were used in data analysis and interpretation. The study shows that students learned from several modes, such as online classes using computers, mobile devices, and other electronic devices such as radio and television. Some students just self-study. It shows a gap in access to online learning between students who had access to online classes and students who studied on their own. The majority of the students preferred to study at home. Among students staying at home, the majority of them were given a separate room to study in, while others studied in a common room. Despite the variable access to online classes, most of the students performed the given assignments. The persistence of the digital divide has posed challenges to education, but the unwavering dedication of students and parents to learning emphasizes its enduring importance. This situation underscores the urgent need for a more equitable and inclusive educational system in the future.